PELATIHAN LITERASI SOSIAL BERBASIS BUDAYA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH GURU SEKOLAH DASAR - Iqnatia Alfiansyah,; Arya Setya Nugroho, (JURNAL PENGABDIAN MANDIRI, 2022)
Social literacy is part of the National Literacy Movement (GLN) launched by the government which encourages people to be able to think scientifically, especially in elementary schools (SD). The ability to think scientifically instilled in elementary age aims to produce a generation that is qualified and able to compete globally, so that teachers who have special abilities in scientific thinking are needed. The purpose of this activity is to train teachers on social literacy knowledge, knowledge of scientific thinking concepts, levels of scientific thinking, and implementation of social literacy in order to improve scientific thinking skills for elementary school children. Activities are carried out by holding social literacy training through the delivery of materials and the provision of cultural-based assignments. The service team from PGSD UM Gresik wants to provide assistance to several elementary school teachers in Gresik so that they can carry out more innovative and creative learning.